Analysis of Using Technology In Physical Education: Systematic Literature Review - S, Adi; Redy Utama, Made Bang; Arba, Fasi Kulisan; Ihsani, Sri Indah; Aliriad, Hilmy; Fahri, Achmad Syakur (UNIVERSITAS NEGERI MAKASSAR, 2025)
The purpose of this research is to look into the use of technology analysis in physical education. The PRISMA standards for systematic reviews and meta-analyses were followed in this review investigation. The study must have been published within the prior five years, from 2020 to 2025. In the search procedure, the following keywords are used: (1) physical education and (2) technology. The search engines Scopus (Science Citation Index Expanded; Social Science Citation Index; Arts & Humanities Science Citation Index). This evaluation included the results of 10 articles. The study revealed two key findings: firstly, Physical Education Pre-Service Teachers (PPETs) frequently employed technology for planning, instructing, and assessing secondary PE classes while also encountering notable barriers in its implementation. Secondly, systematic instruction led to a significant increase in evaluation scores, highlighting the efficacy of structured teaching methods. Additionally, discussions in the article addressed theoretical and practical implications, limitations, and future directions, emphasizing the importance of integrating technology with a clear pedagogical purpose to impact student learning. Technology integration in physical education has enhanced teaching methods and safety, while e-learning adoption in Indonesia requires infrastructure improvements. Additionally, challenges persist in healthcare, including evaluating vaccine models and implementing blockchain technology.